2012
DOI: 10.1111/j.1469-8749.2012.04334.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving upper limb motor functions through action observation treatment: a pilot study in children with cerebral palsy

Abstract: Aim  The aim of this randomized controlled trial was to assess whether action observation treatment may improve upper limb motor functions in children with cerebral palsy (CP). Method  All children with CP admitted to our unit for rehabilitation from May 2009 to May 2010 were eligible. Inclusion criteria were age between 6 years and 11 years, an IQ of at least 70, and no major visual and/or auditory deficits. Fifteen children were enrolled and randomly assigned to either a case group (n=8; four males, four fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
146
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(159 citation statements)
references
References 33 publications
(59 reference statements)
6
146
0
7
Order By: Relevance
“…54,56 Mirror therapy creates a visual illusion of a functional impaired arm using a mirror reflection of the unimpaired arm. Movements of the unimpaired limb are performed while watching its reflection in a mirror that shows the image of the unimpaired limb superimposed over the impaired limb.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…54,56 Mirror therapy creates a visual illusion of a functional impaired arm using a mirror reflection of the unimpaired arm. Movements of the unimpaired limb are performed while watching its reflection in a mirror that shows the image of the unimpaired limb superimposed over the impaired limb.…”
Section: Discussionmentioning
confidence: 99%
“…56 A number of studies reported different domains of outcome (eg, activity, participation) 25,33,36 or different times for follow-up 34,39,43 in separate papers. Details of each intervention and duration, frequency, and intensity of intervention for control and comparison groups are summarized in Table 2.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Results in stroke were encouraging, 4,7,8 but few studies have assessed AO therapy in children with CP. Buccino et al 9 undertook a pilot study of 15 children aged 6 to 11 years with hemiplegia or tetraplegia. Children attended 15 physiotherapist-led rehabilitation sessions at a clinical centre.…”
mentioning
confidence: 99%